Review of the Implementation of Electronic Medical Records Using the HOT-FIT (Human, Organization, Technology, Benefit) Method at Bhayangkara Hospital TK II Sartika Asih Bandung - Nailah Rifdah Ramadhani; Intan Pujilestari (CV. AFDIFAL MAJU BERKAH, 2025)
The rapid digitalization of healthcare systems has accelerated the adoption of Electronic Medical Records (EMRs) globally, yet implementation challenges persist across diverse healthcare settings. This study evaluates EMR implementation at RS Bhayangkara TK II Sartika Asih Bandung using the HOT-FIT (Human, Organization, Technology, Benefit) model to assess whether the hospital meets the criteria for effective digital transformation. A descriptive qualitative research design was employed, utilizing observation and semi-structured interviews as primary data collection methods. The study population comprised 25 medical record information officers (PMIK) from outpatient registration, inpatient registration, emergency department, and casemix units, with key informants selected through purposive sampling. Data were analyzed using thematic analysis to identify patterns across the HOT-FIT framework components. Results revealed strong performance in Human and Organization aspects, characterized by high user adaptability, positive acceptance rates, effective